2020
DOI: 10.1111/jocs.15213
|View full text |Cite
|
Sign up to set email alerts
|

Management of cardiovascular diseases in HIV/AIDS patients

Abstract: Human immunodeficiency virus (HIV) infection/acquired immunodeficiency syndrome, a pandemic in the current population causes severe weakness of the body's immune system making the infected patient more vulnerable to life-threatening conditions. The disease predisposes the infected patient to several cardiovascular diseases and cerebrovascular diseases such as heart failure and stroke. The decline in CD4 cells following HIV infection, vulnerability to opportunistic infections and underlying HIV pathology plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Specifically, HIV may predispose individuals to CVDs and cerebrovascular diseases, such as heart failure and stroke. 33 The decline in CD 4+ T cells, susceptibility to opportunistic infections, and underlying HIV pathology contribute significantly to the development of cardiovascular manifestations. However, treatment targeting cardiomyopathy in this patient subset is not well recognized.…”
Section: Disparities In Hiv Risk and Complications: Causes And Shared...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, HIV may predispose individuals to CVDs and cerebrovascular diseases, such as heart failure and stroke. 33 The decline in CD 4+ T cells, susceptibility to opportunistic infections, and underlying HIV pathology contribute significantly to the development of cardiovascular manifestations. However, treatment targeting cardiomyopathy in this patient subset is not well recognized.…”
Section: Disparities In Hiv Risk and Complications: Causes And Shared...mentioning
confidence: 99%
“…However, treatment targeting cardiomyopathy in this patient subset is not well recognized. 33 Additionally, PLWH face discrimination in receiving CVD care, highlighting the need for improved frameworks to ensure equitable access to health care. Besides the higher prevalence of traditional risk factors contributing to the development of CVD in PLWH, the CVD-associated outcomes are worse for the racial and ethnic minority PLWH.…”
Section: Disparities In Hiv Risk and Complications: Causes And Shared...mentioning
confidence: 99%
“…HIV destroys CD4+ T lymphocytes in a large amount, so that the body loses its immune function, causes a variety of opportunistic infections or tumors, and causes death (Jabłonowska et al, 2021). Globally, there are at least 36.9 million HIVinfected people, and the trend is increasing year by year (Ashwitha et al, 2021). It is reported that there were 36.9 million HIV respondents in the world in 2018, and 56.19% of the infected people received HIV antiretroviral therapy (ART) (Tabler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%